Rancang Bangun Aplikasi Rekomendasi Asisten Rumah Tangga Untuk Penyalur Tenaga Kerja Berbasis Website (INTEK : Jurnal Informatika dan Teknologi Informasi, 2022)
CV Usaha Karya Mandiri is a service provider engaged in the field of labor distribution agents such as household assistants, semi toddlers, semi elderly, nanny, babysitters, nurse patient or elderly. This process has several obstacles, currently, there is no appropriate information and intermediary to connect customers with labor distributor, because customers in the process of searching for housemaids are generally done by contacting friends, neighbors, and closest relatives who can provide recommendations. With the limited time customers have in searching, it can only be done via the internet or come directly to the distributor's location. So that this information search creates obstacles in the desired search based on criteria ranging from price, expertise, and address. To overcome this problem, a website-based application for recommendations for household assistants for labor providers was made. The research was conducted using the Software Development Life Cycle (SDLC) method. So that it can produce applications that are used to search for household assistants based on filter categories and recommendations. Has features such as search based on criteria that can be ordered online through the website, reservation features, consultation, data management, and transaction processing such as labor orders and payment transactions. Testing with the Black Box method Testing the application's features and menus is declared effective and running according to its function.